The quantum theory of fields. - Weinberg, Steven, 1933-2021 (Cambridge University Press, 2005)
The second volume of Weinberg's 'Quantum Theory Of Fields' provides an up-to-date, self-contained account of the methods of quantum field theory and how these have lead to an understanding of the weak, strong, and electromagnetic interactions of the elementary particles.